Gas Chromatographic Mass Spectrometric Analysis of Estrus Specific Volatile Compounds in Buffalo Vaginal Mucus after Initial Sexual Foreplay - karthikeyan, kandasamy; Archunan, Govindaraju (Journal of Buffalo Science, 2013)
Vaginal fluid from buffaloes in estrus, non-estrus condition and saliva from bulls that have licked vaginal mucus were collected. The samples were analysed by gas chromatography-mass spectrometry (GC-MS) in order to evaluate the qualitative differences between the volatile profiles of vaginal mucus and saliva to assess their potential value in buffalo bio-communication. Fifteen different organic compounds were detected. The chemical profiles of estrus vaginal fluid were distinguished significantly by the presence of specific substance, 9-octadecenoic acid (oleic acid) that was not present in non-estrus phase. The results are consistent with the view that the oleic acid acts as chemosignal in a number of mammalian species. Based on the result it is concluded that the volatile substance present in buffalo vaginal fluid may act as a chemical stimulant.